Starteca: participação ativa da biblioteca universitária na constituição da universidade empreendedora - Cassiavilani, Camila (2020)
The advances in Information and Communication Technologies (ICT) have caused changes in all segments of society and have required new forms of action from organizations. In the educational field, universities have also undergone profound changes over time. Since university libraries are units linked to higher-educational institutions, and whose mission must be aligned with the universities; mission, they had to follow these changes. In order to understand how the university libraries can actively contribute to the constitution of an entrepreneurial university, the general objective of this research was to propose the implementation of a space inside the library that encourages entrepreneurship and innovation in academia. The research method used was action-research and the object of study was the Biblioteca Comunitária da UFSCar. The results achieved included: 1) planning a space that encourages entrepreneurship, called Starteca; and 2) Starteca implementation, involving the definition of the organizational structure, services and partnerships. It was concluded that the university library is an active actor in the processes of training entrepreneurs and bringing together private sector and the university, and consequently in the construction of the entrepreneurial university.